Description of an ancient tomb discovered near Stonehaven (Proceedings of the Society of Antiquaries of Scotland, 1854)
An account of the discovery of a stone tomb and its contents near Stonehaven. There is no suggestion of when this tomb could be dated to, but there is a description of the state of decay of the body inside the tomb.